Implementasi Teknologi Informasi Dalam Sistem Perencanaan Rumah Sakit Untuk Meningkatkan Kualitas Pelayanan - Sari, Andi Mu’tiah; HB, Erlina; Rauf, Nur Inayah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
The development of information technology (IT) has had a significant impact on the healthcare sector, particularly in hospital management and planning. Good planning requires accurate, systematic, and easily accessible data so that hospitals can provide quality, efficient services that meet patient needs. However, many hospitals in Indonesia, including those in Makassar, still face challenges in IT implementation, ranging from limited infrastructure, lack of human resource training, and resistance to system change. This community service activity was held on Juni 11, 2025, in Makassar, with the aim of improving the understanding, skills, and readiness of hospital management in implementing information technology in planning systems. The methods used included counseling, technical training, mentoring, and simulations of hospital management software usage. The activity results showed a 75% increase in participant knowledge based on pre- and post-test evaluations. Participants understood basic IT concepts, were able to run simulations of logistics planning and service scheduling, and demonstrated a commitment to integrating technology into hospital operations. This activity demonstrates that strengthening human resource capacity and infrastructure support can accelerate digital transformation in hospitals, thereby improving the quality of healthcare services.